Answer:
The answer is 14.5
Step-by-step explanation:
5x - 2y + 1z = 8 ⇒ 5x - 2y + 1z = 8
-9x + 2y + 2z = 5 ⇒ -9x + 2y + 2z = 5
-9x - 2y - 5z = 4 -4x + 3z = 13
5x - 2y + 1z = 8
-9x + 2y + 2z = 5 ⇒ -9x + 2y + 2z = 5
-9z - 2y - 5z = 4 ⇒ -9x - 2y - 5z = 4
-18x - 3z = 9
-4x + 3z = 13
-18x - 3z = 9
-22x = 22
-22 -22
x = -1
-18x - 3z = 9
-18(-1) - 3z = 9
18 - 3z = 9
- 18 - 18
-3z = -9
-3 -3
z = 3
5x - 2y + z = 8
5(-1) - 2y + 3 = 8
-5 - 2y + 3 = 8
-2y - 5 + 3 = 8
-2y - 2 = 8
+ 2 + 2
-2y = 10
-2 -2
y = -5
(x, y, z) = (-1, -5, 3)
Answer:
26/33
Step-by-step explanation:
The process is:
0.787878
78.7878
78/99x then simplify
Answer:
w=p/2-t
Step-by-step explanation:
Answer:
C.) f(x) = 2x^2 + 4x + 4
Step-by-step explanation:
The equation of the parabola with vertex (h,k) is y=a(−h+x)^2+k.
Thus, the equation of the parabola is y=a(x+1)^2+2.
To find a, use the fact that the parabola passes through the point (2,20): 20=9a+2.
Solving this equation, we get that a=2.
Thus, the equation of the parabola is y=2(x+1)^2+2.
TO STANDARD FORM
= 2*(x^2+2x+1)+2
=(2x^2+4x+2)+2
= 2x^2+4x+2+2
= 2x^2+4x+4